The Significance of the CLDN18-ARHGAP Fusion Gene in Gastric Cancer: A Systematic Review and Meta-Analysis - Zhang, Wei-Han; Zhang, Shou-Yue; Hou, Qian-Qian; Qin, Yun; Chen, Xin-Zu; Zhou, Zong-Guang; Shu, Yang; Xu, Heng; Hu, Jian-Kun (Frontiers in Oncology, 2020)
Objective: The objective of this study was to summarize the clinicopathological characteristics of the CLDN18-ARHGAP fusion gene in gastric cancer patients. Background: The CLDN18-ARHGAP26 fusion gene is one of the most frequent somatic genomic rearrangements in gastric cancer, especially in the genomically stable (GS) subtype. However, the clinical and prognostic meaning of the CLDN18-ARHGAP fusion in gastric cancer patients is unclear. Methods: Studies that investigated CLDN18-ARHGAP fusion gastric cancer patients were identified systematically from the PubMed, Cochrane, and Embase databases through the 28th of February 2020. A systematic review and meta-analysis were performed to estimate the clinical significance of CLDN18-ARHGAP fusion in patients. Results: A total of five eligible studies covering 1908 patients were selected for inclusion in the meta-analysis based on specified inclusion and exclusion criteria. Several fusion patterns were observed linking CLDN18 and ARHGAP26 or ARHGAP6, with the most common type being CLDN18/exon5-ARHGAP26/exon12. The survival outcome meta-analysis of the CLDN18-ARHGAP fusion gene showed that it was associated with overall survival outcomes in gastric cancer (HR, 2.03, 95% CI 1.26–3.26, P < 0.01, random-effects). In addition, diffuse gastric cancer had a greater proportion of CLDN18-ARHGAP fusions than intestinal gastric cancer (13.3%, 151/1,138 vs. 1.8%, 8/442; p < 0.001). Moreover, gastric cancer patients with the CLDN18-ARHGAP fusion gene are more likely to be female or have a younger age, lymph node metastasis and advanced TNM stages. Conclusion: The CLDN18-ARHGAP fusion is one of the molecular characteristics of diffuse gastric cancer and is also an independent prognostic risk factor for gastric cancer. In addition, it is also related to multiple clinical characteristics, including age, sex, lymph node metastasis and tumor stage. However, the mechanism of the CLDN18-ARHGAP fusion gene and potential targeted therapeutic strategies need further exploration.